Hidden Curriculum Dalam Pembinaan Akhlak Peserta Didik Menurut Imam Badruddin Ibn Jama'ah Dalam Tadzkiratussami' - Khoda Siti Khoda; Imas Kania Rahman; Abas Mansur Tamam (TARBAWI : Jurnal Pendidikan Agama Islam, 2022)
This research is aimed at studying a book of Imam Badruddin Ibnu Jama’ah in guiding the attitudes through Hidden Curriculum.  Conceptually the curriculum consists of four dimensions including idea development, written curriculum (curriculum design), curriculum implementation, and curriculum result. Hidden curriculum basically exists in every education process, but it’s not shown in a concept and its own dimension.                Ibnu Jama’ah detailed successful keys of an educator. In relation to teacher/educator concept and its relationship with education, Ibnu Jama’ah detailed its related Islamic norms, which becomes one of the keys of successful students, and shows an example for the students, which include: Norms between educator and him/herself, norms between educator and his/her students, and norms between educator and his/her study.                Process of moral education implementation toward children through education, habituation and good example will help increasing the character education of the students. So that embedding character education to the students sustainably will make the students have good character and can be implemented in daily life.                By implementing education norms in the Tadzkirat al-Sâmi’ wa alMutakallim fî Adab al-’Âlim wa al-Muta’allim book which includes ang Hidden Curriculum through the process of guidance which consists of understanding, habituation, and good example of the teacher or educator can create good students.